Diversity and Distribution of Gastropoda and Bivalvia in Mangrove Ecosystem of Pelangan, Sekotong, West Lombok - Dining Aidil Candri; M. Subandi Rahmani; Hilman Ahyadi; Yuliadi Zamroni (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
One group of invertebrates that live in the mangrove ecosystem is Mollusks of mainly Gastropods and Bivalves. They are associated with mangrove as life, shelter, spawning, and also as a place to get food to support the growth them. The purpose of this reaserch was to look at the effect of mangrove species and substrate type on the distribution Mollusks (Gastropods and Bivalves) in the mangrove ecosystem of Pelangan Village, district of Sekotong, west Lombok regency. This type of reaserch is descriptive explorative. Sampling was done by purposive sampling method with determine tree species, size, and substrate. Repeatation held six times each mangrove species. The results showed that there are 25 speciesd of mollusk in mangrove ecosystem, the most abundant species of gastropod in mangrove species is Clypeomorus moniliferus with a value of 6.9 ind / m2 contained in Osbornia octodonta. As for the distribution of each species of gastropods and bivalves are not affected by the mangrove species, but is influenced by environmental factors which in this case is a substrate.